Acessibilidade de deficientes visuais à imagem de Nossa Senhora Medianeira de todas as Graças na Basílica Medianeira de Santa Maria - RS - Braga, Débora Bichler Duval (2024)
This research, conducted as part of the Postgraduate Programme in Cultural Heritage at the Federal University of Santa Maria (UFSM), within the Area of Concentration and Research Line in History and Cultural Heritage, is part of the study of Marian devotion in the city of Santa Maria, focusing particularly on the image of Our Lady Mediatrix of All Graces at the Basilica Sanctuary dedicated to the saint. This research was dedicated to studying the devotional legacy passed on by Frater Ignacio Rafael Valle, and the intangible and material cultural heritage related to the Basilica, with special attention to the need to make the Marian image exhibited in the Basilica accessible to visually disabled and/or blind people.The primary goal of this research was to design an innovative educational product that enables this audience to interact with the venerated image of the saint through Assistive Technologies (AT), such as description, audio description, QR codes, and Braille. This initiative seeks to promote full inclusion and accessibility in the field of cultural heritage, recognising the Basilica not only as a significant place for religious pilgrimage but also as a cultural and tourist landmark of great importance for Santa Maria and the state of Rio Grande do Sul.The methodology used is based on documentary analysis, bibliographical records and scientific studies on Marian devotion and heritage accessibility. It is a basic study in terms of conceptual analysis of heritage, visual disability and the devotional universe; However, the applied nature becomes evident in the proposal to create an accessible educational resource: a sign with a QR Code, audio description, Open Maps System and Braille writing, designed to make it easier for visually disabled people to interact with the symbolic content of the image of Our Lady Mediatrix. Also, based on the description and audio description prepared as the basis of this study,a 3D modeling of the image of Our Lady Medianeira was created in partnership with the Federal University of Santa Maria and the Farroupilha Federal Institute, providing an accessible tactile experience. This educational product, set in the context of the Mediatrix Basilica Sanctuary, aims to stimulate future research in the field of accessible cultural heritage, as well as contributing to social awareness and expanding the use of assistive technologies to promote inclusion in cultural and religious spaces.